Usulan Perbaikan Sistem Perawatan Pada Mesin Cup Sealer Dengan Menggunakan Metode FMEA dan Fault Tree Analysis di Bagian Produksi CV Rahmat Sanusi Putra - Muhammad Husen; Hendi Iskandar; Darmawan Yudhanegara (Journal of Management and Industrial Engineering (JMIE), 2024)
CV. Rahmat Sanusi Putra is a company that produces bottled drinking water (AMDK) with the brand (nusarina), CV Rahmat Sanusi Putra is faced with problems with its production machines which sometimes experience damage as a result when the production process is hampered and downtime arises. priority scale and causes of damage, and provide recommendations for improvements to reduce the occurrence of machine damage. research using the Failure Mode And Effect Analysis method to find the priority scale and the Fault Tree Analysis method to find the cause of the damage. Data collection through observation and interviews. The highest priority scale obtained on the CV. Rahmat Sanusi Putra in September and November was in the cutting component section with an RPN value of 36. Factors causing machine damage were due to lack of machine maintenance and lack of routine checks resulting in dust or dirt accumulating on the cutting which causes the blade to become blunt and broken. The proposed improvements are to make a monitoring system to carry out proper monitoring, such as doing General Cleaning 2 times and Scouring 2 times in 1 month.